2000
DOI: 10.1897/1551-5028(2000)019<0638:acsamc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

ARCTIC CHAR (SALVELINUS ALPINUS) METALLOTHIONEIN: cDNA SEQUENCE, EXPRESSION, AND TISSUE-SPECIFIC INHIBITION OF CADMIUM-MEDIATED METALLOTHIONEIN INDUCTION BY 17β-ESTRADIOL, 4-OH-PCB 30, AND PCB 104

Abstract: Abstract-In this study, we have examined the basal level expression and tissue-specific expression patterns of metallothionein (MT) in Arctic char following metal and E2 (17␤-estradiol) treatment. To study the gene regulation in Arctic char, the two MT isoforms were isolated from a lambda-ZAP hepatic cDNA library and characterized. Determination of basal MT mRNA and MT expression for 10 different tissues revealed a lack of correlation between MT mRNA and MT levels. The inducibility of MT mRNA and the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…In the present study, all hormone treatments did not result in the significant change of MT mRNA expression in the liver of male mosquitofish as compared with the control. The lack of induction of MT mRNA by the steroid hormones is in accordance with some previous studies on rainbow trout (Olsson et al, 1995) and Arctic Char (Gerpe et al, 2000). However, the changes of MT mRNA in the testis were different from those in the liver of male mosquitofish exposed to steroid hormones.…”
Section: Effects Of Steroid Hormones On Mt Gene Expressionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, all hormone treatments did not result in the significant change of MT mRNA expression in the liver of male mosquitofish as compared with the control. The lack of induction of MT mRNA by the steroid hormones is in accordance with some previous studies on rainbow trout (Olsson et al, 1995) and Arctic Char (Gerpe et al, 2000). However, the changes of MT mRNA in the testis were different from those in the liver of male mosquitofish exposed to steroid hormones.…”
Section: Effects Of Steroid Hormones On Mt Gene Expressionsupporting
confidence: 91%
“…Metallothionein (MT) is a low-molecular weight protein that is involved in the homeostasis of intracellular zinc and copper as well as detoxification of nonessential metals (Gerpe et al, 2000;Huang et al, 2011). Because induction of MT levels has frequently been associated with metal exposure, analysis of MT levels has been used as a biomarker of metal pollution in the aquatic environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E2 treatment resulted in a significant downregulation of MT mRNA expression in two tested tissues of female mosquitofish in the present study. In a previous study, Gerpe et al (2000) reported that MT mRNA expression was not affected in the liver when arctic char (Salvelinus alpinus) were exposed to E2 or mimic estrogens alone, but those compounds could inhibit Cdinduced MT mRNA expression in that tissue. Werner et al (2003) also reported that MT concentrations were significantly reduced in the livers of lake trout exposed to the high and medium concentrations of ethynylestradiol.…”
Section: Modulation Of Mt Gene Expressionmentioning
confidence: 97%
“…Because induction of MT levels has frequently been associated with metal exposure, analysis of MT levels has been used as a biomarker of metal pollution in the aquatic environment. However, MT gene expression was affected by metals (Rhee et al, 2009), chemicals stressors (Gerpe et al, 2000;Werner et al, 2003) and other factors including age, sex and tissue type (Rhee et al, 2009). Although MT genes have been cloned and their expression has been studied in a number of fish species in response to heavy metals, relatively little is known about how those genes are affected by natural or synthetic hormones (Gerpe et al, 2000;Werner et al, 2008;Rhee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%